2018
DOI: 10.14738/assrj.53.3896
|View full text |Cite
|
Sign up to set email alerts
|

Does Brand Image Certainly Mediate Relationships between e-WOM and Purchase Intention? A Case Study of Samsung Smartphone Marketing in Papua

Abstract: The purpose of this study is to investigate the effect and also interrelationship between the variables of e-WOM, brand image, and purchase intention of Samsung smartphones in Jayapura. 100 students from various colleges that spread across Jayapura city were sampled in this research. A quantitative approach with deduction and causal hypothesis testing was employed in this project. Cross-sectional method was also conducted in this study to design the survey with research time dimension. Sampling process of resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…Based on previous research, consumers consider several aspects in deciding to buy a smartphone, for example price, product quality, technology, brand, ease of use, product benefits, recommendations from other parties either directly or in the form of word of mouth (WoM) or e-WoM. Previous researchers considered that aspects of ease of use and benefits were significant in influencing consumers in deciding to buy products (Yu-Chih Huang, et al, 2019), other studies found that WoM or e-WoM had a significant effect (Ivana and Uturestantix, 2018;Iqbal A., et al, 2022), while other researchers assess price, technology are consumer considerations in deciding to purchase products (Nguyen and Phuong, 2020). Meanwhile, some researchers stated that the factors mentioned above did not have a significant effect (Herman, et.al., 2017, Le Minh Duy, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous research, consumers consider several aspects in deciding to buy a smartphone, for example price, product quality, technology, brand, ease of use, product benefits, recommendations from other parties either directly or in the form of word of mouth (WoM) or e-WoM. Previous researchers considered that aspects of ease of use and benefits were significant in influencing consumers in deciding to buy products (Yu-Chih Huang, et al, 2019), other studies found that WoM or e-WoM had a significant effect (Ivana and Uturestantix, 2018;Iqbal A., et al, 2022), while other researchers assess price, technology are consumer considerations in deciding to purchase products (Nguyen and Phuong, 2020). Meanwhile, some researchers stated that the factors mentioned above did not have a significant effect (Herman, et.al., 2017, Le Minh Duy, 2019.…”
Section: Introductionmentioning
confidence: 99%